Reproductive Parameters of Three Populations of Oreochromis Niloticus (Linnaeus, 1758) in the Sudano-Guinean Altitude Zone of Cameroon - Kpoumie, Nsangou Amidou; Tonfack, Achile Peguy; Efole, Ewoukem Thomas; Djikengoue, Kameni Patricia Linda; Fotsa, Jean Claude; Fonteh, Florence; Manjeli, Yacouba (International Journal of Aquaculture Research and Development, 2020)
In order to contribute to the improvement of aquaculture production, reproductive parameters of three populations of Oreochromis niloticus of Cameroon were studied between March and May 2019 at the research station of Foumban. At this effect, a total of 81 parents (27 males and 51 females with respective weight 124 ± 6g and 144 ± 5​​g) coming from three hydrogeographicals origins (Niger, Sanaga and IRAD Station) were randomly distributed in triplicate in nine concrete tanks of a m² each with a sex ratio of one male for two females (1♂/2♀). Throughout the test, six females carrying eggs in the oral cavity were collected in each population and 45 days after the start of the trial, all the offspring were collected and the adults sacrificed. At the end of experiment, the IRAD population presented highest significant values (p ≤ 0.05) regardless of the performances considered. The values of the gonado-somatic and the gonado-metric characteristics significantly lower (p ≤ 0.05) were obtained in Niger population (GSR = 0.04 ± 0.02, GSI = 0.05 ± 0.03 and GMR=0.19 ± 0.08;GMI= 0.24±0.07). Considering sex, males presented the lowest significant values (p ≤ 0.05) for all the characteristics studied (GSR = 0.04±0.01, GSI = 0.04±0.01 and GMR= 0.23±0.08;GMI= 0.29±0.09).
Keywords: Oreochromis niloticus; population; reproductive performance; gonado-somatic; gonado-metric characteristics.